Local sports public policies put to the test by the COVID 19 pandemic - DIOUF, Djibril (Ecoforum Journal, 2022)
COVID-19 has had a negative impact on different sectors of social life in Senegal, not sparing the public sports policies. This naturally prompted players in the field to adapt to the new context of the pandemic. It was, therefore, necessary to reflect on the readjustments of public sports policies in local communities using a mixed, quantitative and qualitative methodological approach. It was noted, on the one hand, a lethargy of public sports policies, following the advent of COVID-19, and, on the other hand, a redeployment of local sports policies towards the fight against the COVID-19 pandemic. These strategies for readjusting public sports policies at regional level have been based on adaptation strategies focused on available resources, on resources to be acquired and on capacities to be transformed.